Self – Care Training For Wound Diabetic Foot Using Guava Leaves Decoction - Yanna Wari Harahap; Nurlaila Nurlaila; Khairunnisa Butar-Butar; Adi Antoni; Anto Anto (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The complications of diabetes mellitus (DM) is diabetic ulcers. The principles of Preparation of the wound (3 M principles) are cleansing, removing necrotic tissue in the wound, choosing the right topical therapy. The aim of this community service to implementation research result about effectiveness of boiling guava leaves as wound washing for diabetic clients. The community service method was wound care diabetic training through guava leaves boil. The program have done as long as a week which the participant were diabetic client in Sidangkal public health center. Before doing community service, the client experienced on caring wound diabetic was used Na-CL, closed wound with cotton, washed every day, and used insulin as preventive diabetic complication. The result of training, the participant said the information about guava leaves boil was new information for them. And all participant also given positive response for this training. And the lead of public health center also said this program improve the knowledge of clients about caring wound diabetic foot.